Reliability of the electric pulp tester as an indicator of pulpal anesthesia in primary maxillary posterior teeth to assess the need for supplemental injections: An observational clinical study - M Swathi Renuka; Ashwin P Rao; Srikant Natarajan; Y M Karuna; P Anupama Nayak; Shweta Rao (Wolters Kluwer Medknow Publications, 2023)
Background: The primary maxillary molars occasionally remain sensitive during operative procedures even post the buccal supraperiosteal injection. This could be due to the widely flared palatal roots receiving accessory innervation from the palatal nerves. Identifying inadequate anesthesia upfront using the electric pulp test (EPT) would give vital information to the clinician on the need of a supplemental palatal injection. Aim: The aim of this study was to assess and evaluate the reliability of the EPT as an indicator of pulpal anesthesia in primary maxillary molars. Methodology: Fifty one primary maxillary molars were subjected to the EPT following a buccal supraperiosteal injection. During the operative procedure, the " Face Legs Activity Cry Consolability" (FLACC) scores were recorded. The outcome of the EPT was correlated with the results of the FLACC score using Pearson's Chi-square test. Results: The EPT results were correlated to the FLACC scores. Five out of the 10 primary maxillary second molars which responded to the EPT scored 0 on the FLACC scale. The remaining 5 teeth scored 1 on the FLACC scale. The P value was 0.056 which was not statistically significant. This infers that the EPT is not a reliable tool to assess the adequacy of pulpal anesthesia in primary maxillary second molars. Conclusion: From the results of the present study, it can be concluded that the EPT is not a reliable tool to be used as an indicator of pulpal anesthesia in primary maxillary molars.